History of urbanization of Kazakhstan in XVIII–XIX centuries in the conditions of transformation of the traditional Kazakh society - Sametova, G.; Alpysbes, M. (KSU Publ., 2018)
The article considers the key stages of urbanization processes in Kazakhstan in the XVIII–XIX centuries. The processes of city formation of fortresses in the territory of Kazakhstan are considered. The features of the construction of fortresses and military lines in general have been revealed and studied. Studying the history of Kazakhstan cities in the XVIII–XIX centuries allows us to imagine how the economic life of urban settlements was changing, under the influence of what factors these changes took place, what significance they had for the population of cities and districts. Also, the article highlights the role of Kazakh historical figures in the process of urbanization of Kazakhstan in the XVIII–XIX centuries. Considerable attention is paid to revealing, both in common features, and the specificity of the socio-economic and cultural development of the county towns of the region. The authors conclude that the colonial policy of the Russian Empire had a significant impact on the transformation of the social and economic life of the population of the cities of Kazakhstan, had an impact on the socio-cultural processes in the region, and changed the ethnic composition of the urban population.
Дəстүрлі қазақ қоғамының өзгеріс жағдайындағы XVIII–XIX ғғ. Қазақстанның урбанизация тарихы
История урбанизации Казахстана в XVIII–XIX вв. в условиях трансформации традиционного казахского общества
Keywords: urbanization; city; military line; fortress; military colonization; the County town; the colonial policy